Social media and functional deterioration: indicators of problematic use in university students - Carbonell-Colomer, Myriam; Marchena-Giráldez, Carlos; Bernabéu-Brotóns, Elena (Frontiers in Psychology, 2025)
The widespread use of social media among university students has raised concerns about its potentially addictive nature and psychological impact. This study examined usage patterns, indicators of addictive behavior, and dimensions of problematic use among 526 Spanish university students (68.8% female; aged 17–25). Participants completed an ad hoc questionnaire and the Problematic Smartphone and Social Media Use Scales (PSSNUS). The results showed an average of 3.13 h per day spent on social media, with WhatsApp, Instagram, and TikTok being the most frequently used platforms. More than 75% of the participants reported tolerance, and 43.4% of the total participants experienced a relapse (representing 230 individuals out of the 326 who uninstalled a social media platform). Psychological dependence and loss of productivity were the most affected dimensions (especially among women). Correlational analyses revealed associations between problematic use and time spent on mobile devices, number of platforms used, and TikTok consumption. These findings identify a profile of use consistent with addictive indicators of social media use among college students and highlight the need for targeted prevention strategies and further research.